Empowering UiTM students to become future entrepreneurs / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
The participants were enlightened with a talk and sharing session by Dr Maryam Al-Batul Azizuddin, Chief Executive Officer cum Founder of Mary Jardin and Dr Muhammad Al-Athiq Marzuki, Co-Founder of Mary Jardin. Mary Jardin is a brand founded by a medical doctor who specializes in the area of organic natural skin care products and cosmetics. The participants, consisting of the university’s staff and students, were also exposed to entrepre-neurial skills and marketing strategies shared by these doctors from Mary Jar-din. These include setting suitable range of ages, planning goals for business development, understanding customer’s target and mastering the importance of friendly customer service. Effective techniques on entertaining, understanding customer’s target and mastering the importance of friendly customer service.